Body Position Alters Mechanical Power and Respiratory Mechanics During Thoracic Surgery. (February 2020) - Chiumello, Davide; Formenti, Paolo; Bolgiaghi, Luca; Mistraletti, Giovanni; Gotti, Miriam; Vetrone, Francesco; Baisi, Alessandro; Gattinoni, Luciano; Umbrello, Michele
Abstract : BACKGROUND: During thoracic surgery, patients are usually positioned in lateral decubitus and only the dependent lung ventilated. The ventilated lung is thus exposed to the weight of the contralateral hemithorax and restriction of the dependent chest wall. We hypothesized that mechanical power would increase during one-lung ventilation in the lateral position. METHODS: We performed a prospective, observational, single-center study from December 2016 to May 2017. Thirty consecutive patients undergoing general anesthesia with mechanical ventilation (mean age, 68 ± 11 years; body mass index, 25 ± 5 kg·m −2 ) for thoracic surgery were enrolled. Total and partitioned mechanical power, lung and chest wall elastance, and esophageal pressure were compared in supine and lateral position with double- and one-lung ventilation and with closed and open chest both before and after surgery. Mixed factorial ANOVA for repeated measurements was performed, with both step and the period before or after surgery as 2 within-subject factors, and left or right body position during surgery as a fixed, between-subject factor. Appropriate interaction terms were included. RESULTS: The mechanical power was higher in lateral one-lung ventilation compared to both supine and lateral position double-lung ventilation (11.1 ± 3.0 vs 8.2 ± 2.7 vs 8.7 ± 2.6; mean difference, 2.9 J·minute −1 [95% CI, 1.4–4.4 J·minute −1 ] and 2.4 J·minute −1 [95% CI, 0.9–3.9 J·minute −1 ]; P < .001 and P = .002, respectively). Lung elastance was higher during lateral position one-lung ventilation compared to both lateral and supine double-lung ventilation (24.3 ± 8.7 vs 9.5 ± 3.8 vs 10.0 ± 3.8; mean difference, 14.7 cm H2 O·L −1 [95% CI, 11.2–18.2 cm H2 O·L −1 ] and 14.2 cm H2 O·L −1 [95% CI, 10.8–17.7 cm H2 O·L −1 ], respectively) and was higher compared to predicted values (20.1 ± 7.5 cm H2 O·L −1 ). Chest wall elastance increased in lateral position double-lung ventilation compared to supine (11.1 ± 3.8 vs 6.6 ± 3.4; mean difference, 4.5 cm H2 O·L −1 [95% CI, 2.6–6.3 cm H2 O·L −1 ]) and was lower in lateral position one-lung ventilation with open chest than with a closed chest (3.5 ± 1.9 vs 7.1 ± 2.8; mean difference, 3.6 cm H2 O·L −1 [95% CI, 2.4–4.8 cm H2 O·L −1 ]). The end-expiratory esophageal pressure decreased moving from supine position to lateral position one-lung ventilation while increased with the opening of the chest wall. CONCLUSIONS: Mechanical power and lung elastance are increased in the lateral position with one-lung ventilation. Esophageal pressure monitoring may be used to follow these changes.